Early Years Work-Based Learning / A Guide for Students of Early Years and Early Childhood Studies - Farrelly Penny (Learning Matters, 2010)
This text helps students to understand better the context of their work setting and to study more effectively. Editor and Contributors, Introduction: Work-Based Learning for Early Years and Early Years Childhood Studies, The Early Years Sector in the UK: The Current Context, Early Years Study, Becoming an Early Years Professional, Supporting Children's Learning and Development in Practice: Developing Your Specialist Knowledge, Current Debates in Early Years Education and Provision, The Future: Early Years Professional Status, Index.